Do Behaviour and Culture of Occupational Health and Safety (OHS) Matter for the Effectiveness of OHS Programs and Policies in Indonesia? (Empirical Evidence from City of Garut) - Tri Waluyo (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study tries to investigate whether Occupational, Health, and Safety (OHS) behaviour and culture can influence the effectiveness of OHS programs and policies. The author used a qualitative methodology where the collection of data is generated through interviews and direct field observations in 40 companies at the City of Garut. This study found that OHS has been implemented both through the diffusion and the adoption of policies and programs, as well as various implementation techniques. However, the background and motivation for implementation were still caused by things that were instrumental, formal, and fragmented in nature. Therefore, OHS value should be intrinsic to each member of the organization and must be agreed as a shared value. Such an argument endorses an important role of a leader in the company, where one of his or her main tasks is to transform individual values into collective values in the form of safety culture.